Mixed alkali effects in Er3+‐doped borate glasses: Influence on physical, mechanical, and photoluminescence properties. Issue 8 (13th February 2019) - Hu, Qingliu; Wang, Tongyao; Chu, Yushi; Wang, Xin; Du, Yanqiu; Ren, Jing; Yang, Xinghua; Yang, Guang; Kong, Xueqian; Wang, Pengfei
Abstract: Engineering borate glass structure by simple compositional modification is essential to meet the particular demands from both industrial and photonic research communities. In this article, we demonstrate how the mixing of Li2 O with Na2 O, K2 O, or Cs2 O influences the relative abundance of 3‐ and 4‐coordinated borons in the glass network, as exhibited by nuclear magnetic resonance (NMR) and Raman spectra. A systematic study is given of the alkali mixing effect on the glass properties including: glass transition temperature, microhardness, density, refractive index, and particularly the near‐infrared photoluminescence properties (eg, bandwidth and lifetime) of Er 3+ which has been barely studied in mixed alkali borate glasses. It is interesting to note that the glass transition temperature, refractive index and emission lifetime of Er 3+ manifest mixed alkali effect, in sharp contrast with microhardness, density, and emission bandwidth which vary monotonically upon the alkali mixing. The possible causes for the differences are discussed in the light of the compositional dependence of boron species and nonbridging oxygen upon alkali mixing.